Pharmacological activation of transient receptor potential vanilloid 4 promotes triggering of the swallowing reflex in rats - Hossain, Mohammad Zakir; Ando, Hiroshi; Unno, Shumpei; Roy, Rita Rani; Kitagawa, Junichi (Frontiers in Cellular Neuroscience, 2023)
The swallowing reflex is an essential physiological reflex that allows food or liquid to pass into the esophagus from the oral cavity. Delayed triggering of this reflex is a significant health problem in patients with oropharyngeal dysphagia for which no pharmacological treatments exist. Transient receptor potential channels have recently been discovered as potential targets to facilitate triggering of the swallowing reflex. However, the ability of transient receptor potential vanilloid 4 (TRPV4) to trigger the swallowing reflex has not been studied. Here, we demonstrate the involvement of TRPV4 in triggering the swallowing reflex in rats. TRPV4 immunoreactive nerve fibers were observed in the superior laryngeal nerve (SLN)-innervated swallowing-related regions. Retrograde tracing with fluorogold revealed localization of TRPV4 on approximately 25% of SLN-afferent neurons in the nodose–petrosal–jugular ganglionic complex. Among them, approximately 49% were large, 35% medium, and 15% small-sized SLN-afferent neurons. Topical application of a TRPV4 agonist (GSK1016790A) to the SLN-innervated regions dose-dependently facilitated triggering of the swallowing reflex, with the highest number of reflexes triggered at a concentration of 250 M. The number of agonist-induced swallowing reflexes was significantly reduced by prior topical application of a TRPV4 antagonist. These findings indicate that TRPV4 is expressed on sensory nerves innervating the swallowing-related regions, and that its activation by an agonist can facilitate swallowing. TRPV4 is a potential pharmacological target for the management of oropharyngeal dysphagia.